Capital Requirements, Monetary Policy, and Aggregate Bank Lending: Theory and Empirical Evidence - THAKOR, ANJAN V. (Journal of Finance, 1996)
ABSTRACT Capital requirements linked solely to credit risk are shown to increase equilibrium credit rationing and lower aggregate lending. The model predicts that the bank's decision to lend will cause an abnormal runup in the borrower's stock price and that this reaction will be greater the more capital‐constrained the bank. I provide empirical support for this prediction. The model explains the recent inability of the Federal Reserve to stimulate bank lending by increasing the money supply. I show that increasing the money supply can either raise or lower lending when capital requirements are linked only to credit risk.